THE DEPTH OF APPROVAL OF DOMESTIC SOCIO-CULTURAL TRADITIONAL KNOWLEDGE DISRTIBUTION IN THE EASTERN LANDSCAPE OF EUROPE (ON MATERIALS OF THE SECOND HALF OF THE 19TH CENTURY) - Чумак, М. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2019)
The socio-cultural ideal of the national scientific and educational intelligentsia was determined by such features as: the priority of value orientations, the deep desire to teach and study, humanist orientation, political and radical attitude to the existing regime, the desire for practical implementation of association. The intellectuals of the XIX century differed from previous generations by the established standards of personal behavior in society, reproducing indifferent attitude to material goods. They sowed the eternal, spiritual and wise in the graceful socio-cultural field, which collectively targeted generations to popularize the spiritual and national treasure among different sections of the population. It should be emphasized that the above-mentioned features became the fundamental characteristic of the domestic scientific and educational intelligentsia, which was incommensurable with the phenomenon of "intellectual" popular in Western Europe. One more important feature, in the context of a stated problem, was that the influence of global processes on the formation of the domestic scientific and educational intelligentsia was reinforced by the "spirit" of time, which, in itself, was the starting trajectory of socio-cultural development of every domestic corner. In such historical conditions, the phenomenon of the existing intelligentsia acquired an intellectual color, since the active development of the classical higher education concentres in the constructed straight lines at the level of four points of the horizon already testified about the corresponding level of socio-cultural development of Ukraine at that time. Reflection of the studied issues allowed us to conclude that the "growth" of pedagogical potential in domestic terrain was the result of the progressive activity of educators in different corners of our country and beyond. The results of the study showed that the progressive changes of the Ukrainian intelligentsia, which were strengthened by the worldview of European innovation, became a part of a broad socio-cultural practice of historical development. Domestic educators devoted themselves to unselfish service to their people, within the framework of which progressive educational and scientific projects were realized